Control of wrist position and muscle relaxation by shifting spatial frames of reference for motoneuronal recruitment: possible involvement of corticospinal pathways - Raptis, Helli; Burtet, Liziane; Forget, Robert; Feldman, Anatol G. (The Journal of physiology, 2010)
It has previously been established that muscles become active in response to deviations from a threshold (referent) position of the body or its segments, and that intentional motor actions result from central shifts in the referent position. We tested the hypothesis that corticospinal pathways are involved in threshold position control during intentional changes in the wrist position in humans. Subjects moved the wrist from an initial extended to a final flexed position (and vice versa). Passive wrist muscle forces were compensated with a torque motor such that wrist muscle activity was equalized at the two positions. It appeared that motoneuronal excitability tested by brief muscle stretches was also similar at these positions. Responses to mechanical perturbations before and after movement showed that the wrist threshold position was reset when voluntary changes in the joint angle were made. Although the excitability of motoneurons was similar at the two positions, the same transcranial magnetic stimulus (TMS) elicited a wrist extensor jerk in the extension position and a flexor jerk in the flexion position. Extensor motor‐evoked potentials (MEPs) elicited by TMS at the wrist extension position were substantially bigger compared to those at the flexion position and vice versa for flexor MEPs. MEPs were substantially reduced when subjects fully relaxed wrist muscles and the wrist was held passively in each position. Results suggest that the corticospinal pathway, possibly with other descending pathways, participates in threshold position control, a process that pre‐determines the spatial frame of reference in which the neuromuscular periphery is constrained to work. This control strategy would underlie not only intentional changes in the joint position, but also muscle relaxation. The notion that the motor cortex may control motor actions by shifting spatial frames of reference opens a new avenue in the analysis and understanding of brain function. Voluntary wrist motion may involve descending influences from the brain that reset the threshold (referent) position at which muscles are recruited. This hypothesis was confirmed in experiments in which subjects restored the initial level of wrist muscle activity after moving their wrist to a new position. Responses to mechanical perturbations before and after movement showed that the wrist muscle threshold position was reset when voluntary changes in the joint position were made. This resetting was reflected in concomitant changes in descending corticospinal excitability. The notion that the motor cortex may control motor actions by pre‐determining the spatial boundaries in which muscles are constrained to work opens a new avenue in the analysis and understanding of brain function.